Spatially resolved spectroscopy across stellar surfaces: I. using exoplanet transits to analyze 3-D stellar atmospheres - Dravins, Dainis; Ludwig, Hans-Günter (Arxiv, 2017)
CONTEXT: High-precision stellar analyses require hydrodynamic modeling to interpret chemical abundances or oscillation modes. Exoplanet atmosphere studies require stellar background spectra to be known along the transit path while detection of Earth analogs require stellar microvariability to be understood. Hydrodynamic 3-D models can be computed for widely different stars but have been tested in detail only for the Sun with its resolved surface features. Model predictions include spectral line shapes, asymmetries, and wavelength shifts, and their center-to-limb changes across stellar disks. AIMS: To observe high-resolution spectral line profiles across spatially highly resolved stellar surfaces, which are free from the effects of spatial smearing and rotational broadening present in full-disk spectra, enabling comparisons to synthetic profiles from 3-D models. METHODS: During exoplanet transits, successive stellar surface portions become hidden and differential spectroscopy between various transit phases provides spectra of small surface segments temporarily hidden behind the planet. Planets cover no more than about 1% of any main-sequence star, enabling high spatial resolution but demanding very precise observations. Realistically measurable quantities are identified through simulated observations of synthetic spectral lines. RESULTS: In normal stars, line profile ratios between various transit phases may vary by some 0.5%, requiring S/N ratios of 5,000 or more for meaningful spectral reconstruction. While not yet realistic for individual spectral lines, this is achievable for cool stars by averaging over numerous lines with similar parameters. CONCLUSIONS: For bright host stars of large transiting planets, spatially resolved spectroscopy is currently practical. More observable targets are likely to be found in the near future by ongoing photometric searches.